The Memory of Neltume, Chile: The Heritage that Overcomes Negationism (Tempo e Argumento, 2024)
In recent decades, Chilean civil society has been very active in the development of material and intangible heritage around its recent past, with particular emphasis on the appearance of memory sites linked to the serious crimes against humanity committed during the dictatorial period. (1973-1989). In this sense, the historical narrative has focused on considerations about the horror of those events, manifested in museographic scripts and displays on various platforms of those events. The case of the Neltume memory site, in the Los Ríos region, shows a particular difference with this trend, referring to social and political events that unite historical and social subject, with political events that contextualize the conflict between the civil-military dictatorship with resistance to such imposition. Thus, the question that guides us is: What political disputes around memory are unleashed from the use of the heritage declaration as a memorialization device? With this we seek to understand the social and political debates in relation to this declaration of historical monument that shows the tension between deniers and memory activists. In this work we will use press releases, as well as public documentation about the declaration of this historical monument to delve into the problem, putting at the center the battle for memory that is currently being experienced in the Chilean public space. From this we will make conclusions that answer the question posed.
Keywords: heritage; memory; denialism; Neltume; Chile